Kidney Retransplantation with Third Graft and No Nephrectomy-A Successful Surgical Challenge Case Report - Ottaiano, Arthur Degani; Domenico, Bruno Ricardo Di; Avilez, Natalia Dalsenter; Mazzali, Marilda; Lima, Marcelo Lopes (British Journal of Healthcare and Medical Research, 2023)
Renal transplant is the gold standard treatment for patients with end-stage renal disease. Currently, some cases that were previously considered contraindications have become possible to perform. There is no clear limit to the maximum number of retransplants in the literature. In this study, we present the report of a patient who underwent a third renal transplant after the failure of the two previous ones without performing nephrectomy or transplantectomy. A 54-year-old man had undergone two previous kidney transplants (in 2014 and 2018), with failure of both grafts. In 2022, he was admitted again to undergo a third kidney transplant. There was adequate space for vascular anastomosis with the graft, with few calcifications upon palpation and adequate space to accommodate the donated kidney. Vascular anastomoses and modified Lich-Gregoir ureteral reimplantation occurred without complications. There is a debate about the benefit of undergoing subsequent transplants or keeping the patient on dialysis, with little literature available. There is no established theoretical limit to the number of kidneys transplanted in a single individual. Occupied iliac fossae remain a true surgical challenge, especially in cases of third or fourth kidney transplants. However, the recent increase in graft survival in patients undergoing repeated transplants makes this option attractive. Renal retransplantation in the ipsilateral iliac fossa without transplantectomy is surgically challenging. These cases are still not common in the medical literature, and their report is important to increase the existing evidence supporting the effectiveness of repeated renal transplants.